2013
DOI: 10.1371/journal.pone.0060410
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Brain-to-Brain Interface (BBI): Establishing Functional Links between Two Brains

Abstract: Transcranial focused ultrasound (FUS) is capable of modulating the neural activity of specific brain regions, with a potential role as a non-invasive computer-to-brain interface (CBI). In conjunction with the use of brain-to-computer interface (BCI) techniques that translate brain function to generate computer commands, we investigated the feasibility of using the FUS-based CBI to non-invasively establish a functional link between the brains of different species (i.e. human and Sprague-Dawley rat), thus creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
64
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 42 publications
0
64
0
2
Order By: Relevance
“…Yoo et al also reported a functional link between the brains of different species (i.e. human and rat) developed non-invasively using transcranial focused ultrasound [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoo et al also reported a functional link between the brains of different species (i.e. human and rat) developed non-invasively using transcranial focused ultrasound [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently many researchers have attempted to create a functional interface between the two brains, often called a brain-to-brain interface (BTBI) [3,4]. For instance, Pais-Vieria et al have established a link between the brains of two rodents and showed that behaviorally meaningful sensorimotor information from one could affect behavior of another in real time even when those animals were separated far apart [3].…”
Section: Introductionmentioning
confidence: 99%
“…In this study M1 neural ensemble was used as a motor information elicitation source in the encoder rat and invasive intercortical microstimulation (ICMS) as corresponding command inducer in the decoder rat’s brain 3 . BBI was also used to successfully establish artificial information transfer pathway from a human to a rat using electroencephalography (EEG) and transcranial focused ultrasound (FUS) to control a simple motion of the rat’s tail using BBI 4 . In a later study, the first direct brain-to-brain interface between two humans was established, which investigated the feasibility of decoding a command from a sender’s brain by EEG and forcing a receiver to follow the command using transcranial magnetic stimulation (TMS) 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 15 years, technologies for non-invasive transmission of information from brains to computers have developed considerably, and today brain-computer interfaces embody a well-established, innovative field of study with many potential applications [12][13][14][15][16]. Recent work has demonstrated fully non-invasive human to rat B2B communication by combining motor imagery driven EEG in humans on the BCI side with ultrasound brain stimulation on the CBI-rat side [17]. However, the realization of non-invasive CBI in humans remains elusive, and adequate methodologies to provide computer-mediated non-invasive brain conscious interventions are lacking.…”
Section: Introductionmentioning
confidence: 99%